PENDIDIKAN ISLAM DI INDIA - Nurhayati Nurhayati; Wasiah Wasiah (CV. ADIBA AISHA AMIRA, 2022)
The purpose of this paper is to discuss the history of Islamic education in India. This mapping is based on a discussion of Islamic education in India; Sayyid Ahmad Khan is known as a reformer of Islamic education in India. This paper aims to reveal the historical flow of the entry of Islam in India in general, then the emergence of Islamic educational institutions initiated by the reformers of Islamic education in India. This paper also uses a literature review study that focuses on content (content analysis), then draws general conclusions about Islamic education in India. The findings of this paper reveal that; 1) the existence of Islam in India is inseparable from the Khulafa ar Rashidin period, the era of the Umayyad and Abbasid dynasties, 2) several Islamic educational institutions that were born from history are Aligarh Muslim University in India, Madrasah Dar al-Uluum Deoban in India, and the Muhammadiyah School Anglo-Oriental College (MAO C) in India, 3) Islamic education reformers are Rabindranath Tagore and Sayyid Ahmad Khan.